AN ACTIVE NEOPROTEROZOIC CONTINENTAL MARGIN OF THE ZAVKHAN MICROCONTINENT (MONGOLIA): ISOTOPIC-GEOCHRONOLOGICAL EVIDENCE - S. I. Shkolnik; E. F. Letnikova; L. Z. Reznitsky (Геодинамика и тектонофизика, 2022)
There have been presented the results of the study of a thick (no less than 2–3 km), extended (for more than 200 km) volcanogenic formation (Tsetsen-Uul or Yargait) in the south of the Zavkhan terrane of the Central Asian fold belt. The formation is an assemblage of frequently intercalating effusive rocks of the subalkaline basalt-andesite-dacite-rhyolite series, their tuffs, tuffites, ignimbrites, and terrigenous rocks. Felsic rocks dominate over basites, and tuffogenic rocks dominate over effusives. There is some evidence that the formation emerged in a subaerial setting, with explosive eruptions, and the petrogeochemical features of the effusive rocks are typical for subduction environment. The felsic effusive rocks have high negative εNd from –11.5 to –12.8 and Early Precambrian model age TNd(DM)=2.4–2.5 Ga, which indicates the presence of an ancient crust at the depth and its involvement in magma. The evidence supports the formation of volcanic rocks within an active continental margin. The continental-margin formation stage ranges from ~860 Ma to ~780 Ma based on the LA-ICP-MS U-Pb dating of zircons.The Tsetsen-Uul (Yargait) formation is similar in structure and composition to the Zavkhan formation of the Zavkhan terrane and the Sarkhoi group of the Tuva-Mongolian massif, and partially overlaps them in formation time. It is concluded that all three volcanogenic formations emerged in the same geodynamic setting and in the same time interval, and are the fragments of a continental volcanic arc belonging to both Zavkhan and Tuva-Mongolian paleomicrocontinents.